Abdominal Obesity as a Risk Factor of Ischemic Stroke Incidence in Lamongan District Indonesia - SITI ROHMATUL LAILY, 101411123010 (2020)
Introduction: One factor that contributes to ischemic stroke is obesity. This research aims to show a positive effect between abdominal obesity and BMI in ischemic stroke. Methods: This study used a case control design. The case group was patients who diagnosed ischemic stroke and the control group was patients who diagnosed but not as ischemic stroke (inflammatory disease, epilepsy, movement disorders and peripheral nerve disorders). The number of samples for each group is 44 which was obtained by carrying out the purposive sampling technique. Waist circumference data was obtained from waist circumference measurements using metline, while BMI is obtained by measuring the weight using TANITA brand digital scales and height using microtoise. The statistical tests used were Pearson parametric correlation test and simple logistic regression analysis. Results: There is a significant relationship between abdominal obesity and p value 0.0000 and BMI with p value 0.0260 for ischemic stroke. The probability of abdominal obesity in ischemic stroke was (1.75), and BMI was (0.794). Conclusion: someone who has abdominal obesity was 1.75 times more at risk of having an ischemic stroke, with a probability event of 85%. The best method of identifying the risk of ischemic stroke was to use the measurement of abdominal obesity.